0083 Slow Wave Activity During Sleep is Associated with Longitudinal Change in Overnight Memory Recall. (27th May 2020) - Buck, C; Parker Fong, K; Linkovski, O; Kawai, M; O'Hara, R
Abstract: Introduction: Duration of slow wave sleep (SWS) declines with age and may not be the most sensitive biomarker for memory in older adults. Analyzing the spectral power of slow wave activity (SWA) (0.5–4 Hz) may provide a more sensitive measure to capture the impact of sleep on memory. We investigated the association of SWA at baseline with the change of overnight memory recall over one year in older adults. Methods: Participants were 42 community-dwelling healthy older adults (22 women and 20 men). We performed a polysomnography (PSG) and list-learning memory tests at baseline (T1) and after a one-year follow-up (T2). The procedure includes, 1) the participants memorized a 16 word list in the evening, 2) after a 5 minute delay, participants wrote down as many words as they could remember (evening recall), 3) overnight PSG was then performed, and 4) the following morning, participants wrote down as many words from the original list from the night before (overnight memory recall). This procedure was repeated at T2. Mixed modeling was utilized to analyze the association between baseline SWA and trajectory of overnight memory recall. Results: For the SWA component, higher relative power of slow oscillation (0.5–1 Hz) during the first ultradian cycle at baseline was correlated with a greater decline in overnight memory recall after 1 year (t = -2.198, p = .034), which covaried for age and gender. There was no correlation with evening recall. Relative power of delta (1–4 Hz) range activity did not show an association with evening and overnight memory recall. Conclusion: Higher relative power of slow oscillation at baseline predicts a greater decline of overnight memory recall. This may indicate a differential effect among the frequency ranges of SWA on longitudinal change in memory in older adults. Support: This work was supported by National Institute of Health grants MH 070886, AG 18784 and AG17824 and the Office of Academic Affiliations, Advanced Fellowship Program in Mental Illness Research and Treatment, Department of Veterans Affairs.